Enhancing low‐temperature SCR deNOx MnCe catalyst based on rice husk char by KOH and H3PO4 activation. Issue 3 (10th November 2021) - Xu, Junchao; Liu, Haoxin; Sun, Yunlan; Zhao, Huaying; Lv, Li; Wu, Yuxin; Zhang, Xiangyang
Abstract: BACKGROUND: It is of great significance industrially to find cheap materials as low‐temperature selective catalytic reduction (SCR) catalyst support. Pyrolyzed rice husk char (RC) is not only cheap, but also has the characteristics of high porosity, large SSA and good adsorption. Therefore, there is emerging interest in RC as an SCR support. The present contribution is a comparative study of low‐temperature SCR manganese–cerium (MnCe) catalysts based on RC activated by potassium hydroxide (KOH) and phosphoric acid (H3 PO4 ), revealing the different mechanisms of improvement in catalytic performance. RESULTS: Mn‐Ce/RCK (catalyst of MnCe loaded on KOH activated RC) has a wider activity temperature window in the range 120–260 °C, while Mn‐Ce/RCP (catalyst of MnCe loaded on H3 PO4 activated RC) can reach the highest NO conversion of 97% at 240 °C. CONCLUSIONS: N2 adsorption–desorption, Fourier transform infrared (FTIR), X‐ray diffraction (XRD), NH3 ‐temperature programmed desorption (TPD) and X‐ray photoelectron spectroscopy (XPS) were used to characterize and analyze their catalytic performance. The N2 adsorption–desorption and NH3 ‐TPD showed that Mn‐Ce/RCK has a larger SSA and more acid sites than those of Mn‐Ce/RC and Mn‐Ce/RCP. XRD indicated that Mn‐Ce/RCP has a better dispersion than that of Mn‐Ce/RCK. FTIR showed that Mn‐Ce/RCP had more oxygen (O)‐containing functional groups. The XPS revealed that Mn‐Ce/RCP has higher ratios of Mn 4+, Ce 3+ and Oβ . © 2021 Society of Chemical Industry (SCI).